SHORT COMMUNICATION Impact of Climate Change on Land use/Land cover of Chakwal District: SHORT COMMUNICATION Impact of Climate Change on Land use/Land cover of Chakwal District - Ali Safi, Mirza Wajid; Siddiqui, Saima; Rehman , Naveed-ur- (International Journal of Economic and Environmental Geology, 2024)
SHORT COMMUNICATION Impact of Climate Change on Land use/Land cover of Chakwal District